2017
DOI: 10.1002/14651858.cd011197.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation for adults with atrial fibrillation

Abstract: Due to few randomised patients and outcomes, we could not evaluate the real impact of exercise-based cardiac rehabilitation on mortality or serious adverse events. The evidence showed no clinically relevant effect on health-related quality of life. Pooled data showed a positive effect on the surrogate outcome of physical exercise capacity, but due to the low number of patients and the moderate to very low-quality of the underpinning evidence, we could not be certain of the magnitude of the effect. Future high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 90 publications
5
58
0
3
Order By: Relevance
“…adding "AND "Cochrane Database Syst Rev"[Journal]" to the search approach). As an example, we found that the quantity, quality and strength of the evidence base for cardiac rehabilitation varies across various cardiac conditions [36][37][38][39][40][41][42], but strong evidence that cardiac rehabilitation approaches are overall costeffective [44]. Thus, we included YLDs from all cardiovascular conditions as being amenable to physical rehabilitation.…”
Section: Data Selectionmentioning
confidence: 99%
“…adding "AND "Cochrane Database Syst Rev"[Journal]" to the search approach). As an example, we found that the quantity, quality and strength of the evidence base for cardiac rehabilitation varies across various cardiac conditions [36][37][38][39][40][41][42], but strong evidence that cardiac rehabilitation approaches are overall costeffective [44]. Thus, we included YLDs from all cardiovascular conditions as being amenable to physical rehabilitation.…”
Section: Data Selectionmentioning
confidence: 99%
“…1 A recent Cochrane review concluded that exercise-based cardiac rehabilitation in patients with AF improved VO 2 peak , but this conclusion was, according to the authors, based on a small number of studies including few patients. 5 Therefore, further studies are warranted to assess the benefits and risks of such intervention and determine whether it should be offered more generally. 5 In this study, we have defined exercise-based cardiac rehabilitation as physiotherapist-led exercise-based cardiac rehabilitation (PT-X).…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, further studies are warranted to assess the benefits and risks of such intervention and determine whether it should be offered more generally. 5 In this study, we have defined exercise-based cardiac rehabilitation as physiotherapist-led exercise-based cardiac rehabilitation (PT-X).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity also helps to reduce the incidence of AF, where moderate-intensity exercise has been shown to be effective (34). However, a meta-analysis concluded that exercise, among adults with AF, showed no benefits regarding HRQoL (35). As current treatment strategies may involve changes in life-style, it is suggested that a tailored management of each individual with AF is integrated in clinical practice (36).…”
Section: Treatmentmentioning
confidence: 99%
“…In SF-36 is a well-known assessment instrument, takes 10-15 minutes to answer and has been used worldwide in various AF contexts (35,(138)(139)(140)(141).…”
Section: Short-form Health Survey (Sf-36)mentioning
confidence: 99%